Smart-Med Bottle with Clever-Twist Cap (CTC) / Jasmin llyani Ahmad, Marlia Idrus and Haziah Sa'ari - Ahmad, Jasmin llyani; Idrus, Marlia; Sa'ari, Haziah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
This invention relates to an improved medicine bottle and its cap. The objective of this invention is to facilitate users in order to pour liquid medicine in an intelligent way. It is made in such a way that the patient or user did not have to pour the medicine on related accessories such as the measurement spoon, measurement cup or syringe separately. The cap was improved by combining the push-pull cap and measuring cup preferably moulded in one piece called Clever-Twist Cap (CTC). While the bottle namely Smart-Med Bottle, is improvised in terms of the maximum ability to grab and hold easily due to the dotted texture on its surface and the bottle shape such that the hand wraps completely around the bottle. Besides, with the non-slippery bottle surface, users can grip the bottle in an effective way. In order to consume the medicine, patient or user just need to pull out the closure cap, turn down the Smart-Med Bottle and twist the Clever-Twist Cap (CTC) to be rotated in a counter-clockwise to allow the liquid medicine to flow through the pouring neck to the measurement cup to get the correct amount of medicine required. Then, to stop the flow the user just twists back the cap in an anti-clockwise direction. Patient or users then can pull up the push-pull cap to direct consume the medicine. The use of Smart-Med Bottle with CTC has commercialization potential where it can save space and cost due to unnecessary related accessories. Overall, with the improvised characteristics such as portable, safe, clean and user friendly make this invention suitable for all range of users or patient.